Present Health Hazard in Glass Industries ai Firozabad, U.P., India - Pathak, Vishal; Sharma, A.; Tiwari, M.K.; Pathak, Prabhat (Asian Journal of Chemistry, 2010)
Glass industries at Firozabad district are completely non-mechanical, age-old, traditionally cottage and household industries. A detailed study of the processes used here and health hazards along with recommendations to encounter these issues have been systematically dealt with in this report.